Case Report: renal allograft infiltration by chronic lymphocytic leukemia successfully treated with zanubrutinib - Abboud, Brian; Rodriguez, Nehemias Guevara; Babar, Arslan; Coery, Noemy; Robbins, Katherine; Kunwor, Ranju (Frontiers in Oncology, 2026)
BackgroundChronic lymphocytic leukemia (CLL) is the most common leukemia in adults. It is characterized by the accumulation of mature monoclonal B lymphocytes. While native kidney infiltration in CLL is relatively common and typically subclinical, involvement of a transplanted kidney is exceedingly rare and may have profound clinical implications.Case SummaryWe present the case of a 65-year-old woman with end-stage renal disease secondary to hypertension and diabetes mellitus who underwent kidney transplantation in 2016. Several years later, she was diagnosed with Rai stage I CLL following imaging and histopathologic analysis of axillary lymphadenopathy. Despite an initially indolent course, she developed worsening renal function in 2025. A biopsy of the allograft revealed CLL infiltration consistent with her prior nodal disease. The patient was started on Zanubrutinib, a Bruton tyrosine kinase inhibitor (BTKi), with stabilization of renal function.ConclusionThis case highlights a rare and clinically significant presentation of CLL involving a renal allograft. As the therapeutic landscape evolves with the advent of BTK inhibitors, prompt recognition and treatment of extranodal CLL involvement may improve outcomes. This case represents only the second reported instance of successful BTKi use for CLL infiltration in a kidney transplant recipient.